Sustainable shelter-site selection under uncertainty: A rough QUALIFLEX method. (February 2019) - Song, Shuyang; Zhou, Hong; Song, Wenyan
Highlights: A new method of shelter site selection for humanitarian relief operation is proposed. A new topic of shelter site selection considering sustainable aspects is tackled. A multi-criteria method of rough QUALIFLEX is developed. A valid mechanism of processing ambiguity and vagueness is devised. Abstract: In recent years, nature disasters have been observed with larger scale and stronger lethality than before. As one of the most crucial links of humanitarian relief operation, shelter site selection has been paid notable attention by the researchers. Nevertheless, subjectivity and vagueness of realistic environment is neglected consequently in most of the previous literature which aims at solving facility location selection problems. Besides, prevailing MCDM methods utilized in related work have poor mechanism dealing with inconsistent data, meanwhile, they are commonly lack of flexibility. In view of the above mentioned facts, an innovative integrated method is developed in this paper. The proposed approach combines the strength of the qualitative flexible multiple criteria (QUALIFLEX) method in manipulating multiple evaluation criteria with heterogeneity and the advantages of interval rough number in blurry information environment. Moreover, social and environmental aspects which are of great significance whereas rarely mentioned are taken into consideration when shelter sites are evaluated. The competence and feasibility of the proposed method is illustrated in a case study in the settings of Wenchuan County, where a serious earthquake struck on 12th May 2008. To verify the validity of the proposed method, a comparative analysis with other related methodologies is provided.